2021
DOI: 10.1002/chem.202102180
|View full text |Cite
|
Sign up to set email alerts
|

Osmaindenes: Synthesis and Reversible Mechanochromism Characteristics

Abstract: A series of novel osmaindenes 1-6 bearing different substituents (CF 3 , H, I, Br, OCH 3 , N(Ph) 2 ) has been synthesized by nucleophilic reaction of water with the corresponding aromatic osmanaphthalyne complexes. All osmaindenes 1-6 have been characterized by elemental analysis (EA) and nuclear magnetic resonance (NMR) spectroscopy, although the low solubilities of 3 and 4 precluded the accumulation of their 13 C NMR spectra. Osmaindenes 2, 3 and 5 have also been characterized by single-crystal X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…What excited us was the reversible mechanochromic behavior. Learning from the recovery treatment methods of other mechanochromic molecules, 43,[47][48][49] we recrystallized the ground powder with a mixed solution of DCM and n-hexane (v/v, 1/1), and found that the recrystallized powder basically recovered its original state in terms of color, fluorescence and absorbance. We speculated that during recrystallization, because the ground powder was dissolved in the solvent, compared with the solid state, the molecule had enough free volume to meet the requirement of reversible isomerization, thus realizing the transformation from the MC state to the SP state.…”
Section: Mechanochromic Propertiesmentioning
confidence: 99%
“…What excited us was the reversible mechanochromic behavior. Learning from the recovery treatment methods of other mechanochromic molecules, 43,[47][48][49] we recrystallized the ground powder with a mixed solution of DCM and n-hexane (v/v, 1/1), and found that the recrystallized powder basically recovered its original state in terms of color, fluorescence and absorbance. We speculated that during recrystallization, because the ground powder was dissolved in the solvent, compared with the solid state, the molecule had enough free volume to meet the requirement of reversible isomerization, thus realizing the transformation from the MC state to the SP state.…”
Section: Mechanochromic Propertiesmentioning
confidence: 99%
“…[ 13 ] Since then, metal heterocyclic compounds have developed rapidly. Metal heterocyclic compounds reported to date include metallabenzenes, [ 14‐15 ] metallafurans, [ 16 ] metallapyridines, [ 17‐18 ] metallabenzynes, [ 19 ] metallaindenes, [ 20‐21 ] metallanaphthalenes, [ 22‐24 ] metallanaphthalynes, [ 25‐28 ] metallaanthracene, [ 29 ] metallaphenanthrene, [ 30 ] metallaphenanthryne, metallaanthracyne, [ 31,32 ] metallapentalynes, and metallapentalenes. [ 33‐46 ] Among this range of metallaaromatics, fused ring tricyclic or polycyclic metallanaphthalenes are still relatively scarce, [ 47‐49 ] which is mainly due to the paucity of available synthetic methods.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Our continuous efforts to expand the unique metallaaromatic systems have led to the discovery of a series of osmanaphthalynes decorated with diverse substituents as well as the first examples of α‐osmaphenanthryne and α‐osmaanthracyne. [ 25‐28,31 ] These complexes were synthesized by thermal intramolecular C—H activation of the phenyl substituent of an alkenylcarbyne ligand (heating method) or a highly efficient, and mild visible‐ light‐induced strategy (Scheme 1a). During these studies on the chemistry of novel metallaaromatic complexes, we found that these osmapolycycles can exhibit nucleophilic reactivity and display potential electronic communication properties, reversible mechanochromism characteristics.…”
Section: Background and Originality Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanochromic materials have been widely used in data storage, information encryption and sensors due to their simple operation, obvious and fast response (Perruchas et al, 2010;Zhang et al, 2017;Seki et al, 2017;Ito et al, 2008;Song et al, 2018;Li et al, 2019;Zhu et al, 2020). The emission color of mechanochromic materials usually have wide luminous range, covering the entire visible region and even reaching in the near-infrared region (Seki et al, 2017;Zhang et al, 2021;Li et al, 2021). Based on their different phenomenons, mechanochromic materials can be divided into various classes (Figure 1): reversible and irreversible mechanochromism, two-color and multicolor mechanochromism, turn-on and turn-off typed mechanochromism (Yang et al, 2018;Liu et al, 2019;Yang W et al, 2020;Fan et al, 2021;Qian et al, 2021).…”
Section: Introductionmentioning
confidence: 99%